2017
DOI: 10.1111/1753-6405.12600
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of using telehealth for the provision of healthcare to Aboriginal and Torres Strait Islander people: a systematic review

Abstract: Objective: To examine reported outcomes of health services delivered by telehealth to Indigenous Australians.Methods: Systematic review of the literature. Searches were conducted to identify articles that reported a telehealth service used to provide clinical services to Indigenous Australians. Articles were screened for inclusion using pre-defined criteria. Findings were synthesised narratively and reported using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 27 publications
(62 reference statements)
3
102
0
Order By: Relevance
“…Telehealth, the provision of health‐related services and information using telecommunication‐based technologies, is under‐utilized and has been adopted in few Australian government‐funded initiatives. The primary exception is videoconference consultations between a specialist clinician and patient . This is in stark contrast to the high uptake of mobile health by individuals, globally .…”
Section: Introductionmentioning
confidence: 97%
“…Telehealth, the provision of health‐related services and information using telecommunication‐based technologies, is under‐utilized and has been adopted in few Australian government‐funded initiatives. The primary exception is videoconference consultations between a specialist clinician and patient . This is in stark contrast to the high uptake of mobile health by individuals, globally .…”
Section: Introductionmentioning
confidence: 97%
“…Telehealth is contributing to positive changes in our health system and this is evidenced in our recent studies highlighting the value of telehealth for Aboriginal and Torres Strait Islander people. A systematic review of the outcomes of using telehealth for the provision of care to Aboriginal and Torres Strait Islander people reported improved social and emotional wellbeing, clinical outcomes and access to health services . Other benefits included improved screening rates and reduced need for travel .…”
mentioning
confidence: 99%
“…The DRUID study reported above showed an inverse relationship between socio-economic status (SES) and diabetes among younger Indigenous clients. This relationship was true even when the diagnosis of diabetes was not apparent in the younger client group 37 . Such an inverse correlation related to the SES directs the need for distinctly separate care programs dependent on the age of the client and also considering their social circumstances.…”
Section: Socio-economic Statusmentioning
confidence: 86%
“…Several telehealth interventions for Indigenous Australians have been successfully used to date in mental health care, oncology services, and retinopathy screening 69 . Based on these findings, it seems logical to extrapolate that telehealth can be a useful option for Indigenous patients with diabetes, for their continued care.…”
Section: Australian Indigenous People and Telehealthmentioning
confidence: 99%
See 1 more Smart Citation